Elimination of Signaling by the Luteinizing Hormone Receptor Reduces Ocular VEGF and Retinal Vascularization during Mouse Eye Development. (3rd October 2018) - Movsas, Tammy Z; Sigler, Robert; Muthusamy, Arivalagan
ABSTRACT: Purpose/Aim : Vascular endothelial growth factor (VEGF) dysregulation is implicated in the pathogenesis of retinopathy of prematurity (ROP). Identifying the factors that contribute to VEGF regulation during normal retinal vascularization is the key to ROP prevention. Currently, physiologic hypoxia is thought to be responsible for retinal VEGF regulation in utero. However, a potential hormonal contribution to VEGF regulation during eye development has not been fully investigated. The placental hormone, human chorionic gonadotropin and the pituitary hormone, and luteinizing hormone (LH) induce VEGF expression in several tissue types. Both of these gonadotropins activate the same LH receptor (LHR) in the human body; LHRs are expressed in the retina. In this study, we aimed to show that LHR signaling participates in VEGF regulation in the developing eye. Methods : When offspring from breeding pairs of LHR knockout mice (lhrkos) reached 21 days old, eyes and serum were extracted from homozygote lhrkos and wildtype (WT) siblings. VEGF levels were measured using Mouse VEGF Quantikine immunoassay kit. Retinas were incubated with isolectin for endothelial cell staining, flat mounted and imaged by confocal microscopy. Retinal vascular density was quantified using Imaris software. Some eyes were sectioned and stained for histopathologic review. Results : Ocular VEGF and retinal vascular volumes were significantly reduced by ~ 15% in lhrko eyes. Serum VEGF was not changed. The lhrko retinas did not display any anomalies. Conclusions : We provide evidence that LHR signaling plays a role in VEGF regulation and vascularization in the developing eye. Given that human preterm infants may have altered LHR-activity, the effect of gonadotropins on eye development should be further studied to identify novel strategies for ROP prevention.